Hypoglycemic Activity of Aqueous Root Bark Extract Zanthoxylum chalybeum in Alloxan-Induced Diabetic Rats - Moses Solomon Agwaya; Peter California Vuzi; Agnes Masawi Nandutu (Journal of Diabetes Research)
Background. Medicinal plants offer cheaper and safer treatment options to current diabetic drugs. The present study evaluated the effect of aqueous root bark extract of Zanthoxylum chalybeum on oral glucose tolerance and pancreas histopathology in alloxanized rats. Method. Diabetes was induced in rats by administration of alloxan monohydrate. Root extract of Z. chalybeum was administered to rats at 200 and 400 mg/kg BW daily for 28 days. Blood glucose was measured by glucometer and pancreatic histopathology evaluated microscopically. Results. Initial increase was observed in blood glucose of the rats after oral administration of glucose from time zero. Two hours after treatment with Z. chalybeum, a significant reduction in blood glucose was observed within treatment groups (p<0.05) compared to 0.5 hr and 1 hr. There was no significant difference between treatment group receiving 400mg/Kg BW extract and the normal groups (p=0.27), implying that the former group recovered and were able to regulate their blood sugar, possibly via uptake of glucose into cells. The reversal in pancreatic histopathology further supports the protective effect of Z. chalybeum extract towards diabetic damage. Conclusion. Extract of Z. chalybeum is effective in controlling blood glucose in diabetes and protecting pancreatic tissues from diabetic damage.